Determinants of corporate pension funding strategy - Francis, Jere R.; Reiter, Sara Ann (Journal of Accounting and Economics, 1987)
Several hypotheses concerning pension funding strategy are tested in a cross-sectional regression model on a sample of 255 firms. Results are consistent with the following explanations: (1) finance incentives (tax benefits and financial slack) for high-level funding, (2) labor incentives for low-level funding, and (3) financial statement incentives relating to political costs for high-level funding and debt contracting costs for low-level funding. Pension funding strategy appears to be complex, involving tradeoffs between funding incentives. The nature of these interactions and tradeoffs remains to be clarified through future research.